HOW TO IMPLEMENT SPEAKING STRATEGIES: STUDENTS’ REPORTED ACCOUNTS IN ONE ACADEMIC YEAR - Lesta Fina (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: The aim of this study was to investigate students’ speaking problems in the third semester and the strategies used in overcoming their speaking problems in the fourth semester at University of Islam Malang. The sample of this research were 3 representative students of each class in the fourth semester who got A score in speaking from semesters 1-3. The researcher employed descriptive-qualitative method. The instrument of this research was conducted through interviews.              The findings research showed that students had some speaking problems in the third semester. The problems were afraid of making mistakes, feeling insecure, and lack of vocabulary. All those problems occurred when they spoke English in the classroom. The main problem that often occurred in students speaking English was feeling insecure. To solve their speaking problems in the third semester, students used several strategies that were implemented in the fourth semester including speaking practice and preparation, having good interaction, and learning by using media. Among all the strategies that were often used by students to overcome their speaking problems were practice and preparation.In addition, this study was expected to be useful for teachers in providing theories related to methods or techniques for teaching students speaking strategies. Secondly, for the students, this study could provide information for students related to students speaking difficulties and strategies used for improving their speaking skills. There were several suggestions, for teachers, students, and future researchers. Teachers should be able to practice and prepare the strategies in teaching and learning activities in order the students could be easier to understand the lesson that they gave. Teachers could prepare with creative material so that the students were more interested in learning speaking English. Then, students could practice their speaking English with their friends in order they could be more fluent in speaking English. Also, students could prepare before getting presentations in order they could reach good results. Furthermore, the strategies used by students in overcoming speaking problems could be examined more deeply by future researchers. They could also look for students' speaking strategies from the lowest score to the highest score. Keywords: Speaking skills, Students problems, Students strategies